Electrochemiluminescent and electroluminescent devices containing polypyridine transition metal complexes - Bloom, Corey J., author; Elliott, C. Michael, advisor (Colorado State University. Libraries, 2003)
Polypyridine coordination complexes of transition metal cations, most notably tris(2,2'-bipyridine)ruthenium(II)-based compounds, “[Ru(LL)3]”, have a number of properties which make them of interest for both fundamental and applied studies. Stability in a number of oxidation states, along with interesting photochemical and photophysical behavior (including excited states that are in some cases relatively long-lived), are among the potentially useful characteristics of these complexes. Extensive research toward understanding the fundamental nature of these materials has brought the field to a point where the relationships between chemical structure and physical behavior of these metal complexes are well understood. As a consequence, it is now possible to predictably control the properties of these complexes through intelligent synthetic design. Using this knowledge, several materials composed of carefully designed and treated polypyridine metal complexes are described here for use in solid state devices exhibiting emission of light driven by electrical energy.

Light emitting devices based on solid thin layers of organic compounds and/or inorganic coordination complex materials fall into two general categories, electrochemiluminescent (ECL) and electroluminescent (EL) systems. The basic description of the two device motifs is quite similar; however, there are a number of critical differences in the mechanisms by which they operate. These considerations in turn dictate the choices of materials employed in the construction of the two types of devices. The introductory chapter in this work describes in detail the conceptual differences between ECL and EL devices, and the resulting materials requirements.

In the second chapter, an ECL system is described based on a substituted [Ru(LL)3] monomer complex which exhibits intense emission following either photo- or electrochemically-generated excitation. A solid state “sandwich cell” device is constructed following thermal polymerization of the complex to yield electrochemically active thin films. The performance of this device is reported, and is found to be superior to previously reported similar ECL devices, owing to the rational design of the emitting material.

In the third chapter, a series of three polymerizable complexes, including the same [Ru(LL)3]-based complex used in the ECL devices along with two similar compounds, is examined. In this work the electronic properties of the three films are studied after careful electrochemical reduction to yield conductive polymers, with emphasis on conductivities and work functions. These materials are considered for use as the cathode layers for EL devices employing commonly reported emissive compounds. The reduced [Ru(LL)3] conducting polymer with the lowest work function was successfully used as a cathode in devices with two common EL materials. These results sufficed as proof-of-concept for the use of reduced coordination complexes as cathodes in EL devices, but their performance was less than ideal. The inferior performance of these devices is most likely due to the inherent limitations imposed by the use of compounds that necessitated thermal polymerization, as well as the need for electrochemical treatment prior to device construction.

Finally, the fourth chapter describes a related set of three coordination complexes of ruthenium and chromium (discrete molecules rather than polymers) that are also electrochemically reduced and subsequently used as cathode materials for EL devices. Flowever, these complexes can be vapor deposited in the conductive state, and thus have important advantages in actual devices. The performance of systems including layers of these vapor deposited complexes is evaluated and is significantly improved over those devices reported in the previous chapter.
Keywords: analytical chemistry; materials science